Understanding nutrition : Australia and New Zealand edition - Whitney, Eleanor Noss; Cameron-Smith, David; Walsh, Adam; Whitney, Eleanor Noss; Rady Rolfes, Sharon (South Melbourne, Victoria : Cengage Learning, 2014)
Understanding Nutrition is a practical and engaging introduction to the core principles of nutrition. Building upon Ellie Whitney and Sharon Rady Rolfes' classic text, this second Australian and New Zealand edition equips students to optimise health and wellbeing.
1. An overview of nutrition -- 2. Planning a healthy diet -- 3. Digestion, absorption and transport -- 4. The carbohydrates: sugar, starch and dietary fibre -- 5. The lipids: triglycerides, phospholipids, and sterols -- 6. Protein: amino acids -- 7. Metabolism: transformations and interactions -- 8. Energy balance and body composition -- 9. Weight management: overweight, obesity and underweight -- 10. The water-soluble vitamins: B group vitamins and vitamin C -- 11. The fat-soluble vitamins: A, D, E, and K -- 12. Water and the major minerals -- 13. The trace minerals -- 14. Fitness: physical activity, nutrients, and body adaptations -- 15. Life cycle nutrition: pregnancy and lactation -- 16. Life cycle nutrition: infancy, childhood and adolescence -- 17. Life cycle nutrition: adulthood and the later years -- 18. Diet related diseases -- 19. The food and water supply -- Appendix A. Cells, hormones, and nerves -- Appendix B. Basic chemistry concepts -- Appendix C. Biochemical structures and pathways -- Appendix D. Measures of protein quality -- Appendix E. Nutrition assessment -- Appendix F. Physical activity and energy requirements -- Appendix G. Aids to calculation.
Previous edition: 2011.
Includes bibliographical references and index.
Keywords: Metabolism; Nutrition; Health; Metabolism; Nutrition